Increasing lifting-bag mesh size to reduce codend occlusion in Australian whiting (Sillago spp.) trawls - Broadhurst, Matt K. (Frontiers in Fish Science, 2026)
Some small-meshed fish-trawl codends require so-called “protective,” “strengthening,” or “lifting” bags for structural support, but these can occlude mesh openings and reduce size/species selectivity. This study compared two lifting-bag mesh sizes (94 and 216 mm stretched mesh opening; SMO) surrounding a 46-mm SMO codend in an Australian whiting-trawl fishery. During 37 deployments off Newcastle, New South Wales, compared to the 94-mm lifting bag, the 216-mm lifting bag significantly reduced the catches of juvenile eastern school whiting (Sillago flindersi <17 cm total length; TL) by ~35% and small unwanted velvet leatherjacket (Meuschenia scaber) by ~67%. Total bycatch declined by ~50%. However, ~6% of eastern school whiting ≥17 cm TL also escaped, along with some important byproduct species. Relative size–frequency analysis revealed no significant TL effects for eastern school whiting although there was evidence of fewer individuals being retained with the larger-meshed lifting bag. The data reiterate species-specific lifting-bag effects and the importance of evaluating both conservation benefits and economic impacts when subtly modifying trawl configurations.